Gay Men and the Left in Post-War Britain: How the Personal Got Political - Maynard, Steven (Labour / Le Travail, 2008)
The article reviews the book, "Gay Men and the Left in Post-War Britain: How the Personal Got Political," by Lucy Robinson.
Keywords: BOOKS -- Reviews; GAY Men & the Left in Post-War Britain: How the Personal Got Political (Book); GAY people; Nonfiction; ROBINSON, Lucy

Working Like a Homosexual: Camp, Capital, Cinema - Maynard, Steven (Labour / Le Travail, 2005)
The article reviews the book, "Working Like a Homosexual: Camp, Capital, Cinema," by Matthew Tinkcom.